Protection of Labor in Realizing Labor Welfare in Construction Projects (JIIPE Manyar Gresik Construction Project Study) - Annisa' Carina; Hasbi Hasbi; Linda Kurnia Supraptiningsih; Ratna Fajarwati Meditama (Litbang Pemas - Universitas Islam Lamongan, 2022)
In the current era of 4.0, the job market opportunities for construction services continue to develop. The Java Integrated Industrial and Ports Estate (JIIPE) construction project, which is located in an industrial area in Gresik, is an area development project that is targeted to be able to absorb a workforce of 500 thousand people. The workforce has a role in national productivity and community welfare. Therefore, the human resources of the workforce must be empowered in order to have the competence, skills, and quality optimally. The Construction Services Law Number 2 of 2017 Article 70 stipulates that every construction worker who works in the Construction sector is required to have a Work Competency Certificate. determined based on the certificate held, in addition, labor distribution and protection of workers are also not optimal, for the welfare of workers in construction projects. In this study using descriptive qualitative research . Data were obtained through interview, documentation, observation and questionnaire techniques, sampling using purposive sampling technique. Based on the results of the study, it was found that (1) JIIPE provides opportunities for local residents to become part of the world of work by looking at the appropriate competencies, (2) workers in the JIIPE area are given the opportunity to develop their soft skills. skills by participating in competency development training with output certificates of expertise or competency certificates in accordance with their fields. This is the JIIPE Manyar Gresik development project provide welfare for workers and their families.